The growth of internation arbitration - Waters, Lucy Helena (My University, 1894)
Introduction: With primeval man came dissensions and the earliest record of the duds of men is but one lengthened account of war and discord settled by the word. In the Garden of Eden, personal jealousy led to the first slaughter of man. No thought of glory, no love of home or country, no redress of wrong, no vindication of the right, prompted Cain. In the cry of Goliath of old, “Give me a man that we may fight together, and I will slay him and ye shall be our servants and serve us.” We find typified the thirst for personal glory and desire for conquest as truly as in any later day. In olden times, mere separation by language custom or nature served as a sufficient reason for distrust and enmity. The mere fact that two peoples were separated by mountain range or river seemed sufficient in itself to sow the seeds of hate. This unwise and unjust enmity between nations prevented, as a matter of course, any equitable adjustment of difficulties had such been possible otherwise. Pascal satirizes this inherent enmity in the following: “Wherefore do you kill me?” cries some poor victim of his neighbor’s sword. “What! Do you not dwell on the other side of the water? My friend, if you dwelt on this side, I would be an assassin for then it would be wrong to kill you; but since you dwell on the other side, I am a hero, and it is just to kill you.” Here we have an advanced phrase of Goliath’s motion—not for personal glory but for the aggrandizement of his country, for the glory of those who “dwell on this side of the water.”
Citation: Waters, Lucy Helena. The growth of internation arbitration. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Growth; Arbitration; Foreign; Goliath; Political science; Theses; Manuscripts (documents)